2009
DOI: 10.1088/0031-9155/54/22/003
|View full text |Cite
|
Sign up to set email alerts
|

Radiochromic leuco dye micelle hydrogels: II. Low diffusion rate leuco crystal violet gel

Abstract: Radiation-sensitive hydrogels offer the capability of verifying intricate dose distributions in three-dimensional (3D) space conveniently in a single measurement with sub-millimetre spatial resolution. In this study, a new radiochromic hydrogel called leuco crystal violet (LCV) micelle gel is introduced. Upon irradiation, LCV converts to crystal violet (CV(+)). Triton X-100 micelles are used to provide the required hybrid-interfacing environment to dissolve LCV. The diffusion coefficient of the LCV gel has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
102
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 32 publications
8
102
1
3
Order By: Relevance
“…However, batches do show a large amount of variance and further work reproducing these results is necessary. The proposed gel has a dose sensitivity 80% higher than the original LCV micelle gel developed by Babic et al [1] while still at a similar initial absorbance. In future, we will explore the possibility to develop gels with lower dose-rate dependence and even higher dose sensitivity by expanding the bounds used for recipe optimization, and attempt to modify the preparation methods to produce more consistent results.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, batches do show a large amount of variance and further work reproducing these results is necessary. The proposed gel has a dose sensitivity 80% higher than the original LCV micelle gel developed by Babic et al [1] while still at a similar initial absorbance. In future, we will explore the possibility to develop gels with lower dose-rate dependence and even higher dose sensitivity by expanding the bounds used for recipe optimization, and attempt to modify the preparation methods to produce more consistent results.…”
Section: Discussionmentioning
confidence: 72%
“…Radio-chromic LCV micelle gels manufactured with CTAB surfactant exhibit improved dose sensitivity and comparable initial absorbance when compared to the LCV gel proposed by Babic et al [1]. Unfortunately, these new gels can exhibit undesirable dose-rate dependence (as high as 32% between dose rates of 100 and 600 cGy min -1 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This approach is general and is an active area of research on an industrial scale as society migrates from hydrocarbon solvents to "green chemical syntheses". The initial reports have demonstrated that insoluble leuco dyes can be incorporated into gelatin hydrogels with nonionic surfactants [16,24]. Diffusion measurements revealed that the more water soluble, cationic dye Malachite Green had a higher diffusion coefficient.…”
Section: Fe(iii) 1 -X 2 (480 Nm)mentioning
confidence: 99%